2012
DOI: 10.1596/27436
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture for Inclusive Growth in Uganda

Abstract: is prepared by Sergiy Zorya (ARD), Varun Kshirsagar (AFTAR), Madhur Gautam (SAARD), Willy Odwongo (AFTAR), Jos Verbeek (AFTP2), and Rachel Sebudde (AFTP2). It draws on various background studies recently undertaken for the Uganda Inclusive Growth Project. 2 Inclusive growth is defined as economic growth .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, declining agricultural productivity is a primary contributing factor. A recent study found that over the last fifteen years total factor productivity in agriculture was negative, and that increases in output were due to area expansion rather than intensification and productivity growth (Zorya et al, 2010). Reasons include declining soil fertility, an almost complete reliance on rainfall and inability to compensate for seasonal and monthly variability, land tenure insecurity, and poor market access.…”
Section: (Projected)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, declining agricultural productivity is a primary contributing factor. A recent study found that over the last fifteen years total factor productivity in agriculture was negative, and that increases in output were due to area expansion rather than intensification and productivity growth (Zorya et al, 2010). Reasons include declining soil fertility, an almost complete reliance on rainfall and inability to compensate for seasonal and monthly variability, land tenure insecurity, and poor market access.…”
Section: (Projected)mentioning
confidence: 99%
“…Indeed, a recent World Bank study found that the prospects for agricultural development in Uganda are as good, or better, than they were in Asia and Latin America during their 'agricultural revolutions.' This is due to a number of exogenous factors including accelerated growth and rapid urbanization in Africa, the end of the price decline for agricultural commodities, and the greater availability of improved technological opportunities (Zorya et al, 2010).…”
Section: Uganda's Development Opportunitiesmentioning
confidence: 99%
“…Agriculture continues to be the core sector in the economic development of Uganda [1]. It is also highlighted that agriculture is essential when it comes to sustainable development as well as poverty reduction in developing countries [6]. In this case, it is not surprising that agricultural production, especially by small-scale farmers in developing countries contributes to the sustainability of food security in both rural and urban population.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that more than 60% of Ugandans are engaged in agriculture [6]. In fact, the sector has always been given priority in the national development plan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation